The Selection of the dp Breakup Events from D CH2 Reaction at 500 MeV - Janek, Marian; Trpisova, Beata; Ladygin, Vladimir Petrovich; Piyadin, Semen Mikhailovich (Communications - Scientific letters of the University of Zilina, 2014)
The simulations of dC and dCH2 (CH2 - polyethylene) reactions for different detector configurations were performed at 500 MeV of deuteron energy. We present method by means of which the signal from dp breakup reaction can be separated from the background that mainly comes from the carbon content of the target.